We, Slavs – Tools and Functions of (Re)Constructing Polish Pre-History in Fantasy Literature on the Example of Witold Jabłoński’s Cycle Słowiańska Apokalipsa - Kobus, Aldona (Literatura Ludowa. Journal of Folklore and Popular Culture, 2026)
The article analyzes Witold Jabłoński’s historical fantasy cycle Słowiańska Apokalipsa [Slavic Apocalypse] (2013–2021) as an example of creating an image of preliterate and pre-Christian Polish past in pop cultural circulation. The cycle is inscribed into the genre of Slavic fantasy which, to a large degree, is based on the “phantasm of Slavic tradition” as identified by Maria Janion, which serves important function as a source of collective identity or a reservoir of senses and symbols used to create identity models alternative to the official national and Catholic discourse. Jabłoński’s cycle is focused on creating a model of a pagan martyr or pagan martyrology that would justify the moral superiority of pagans and anti-clerical tone of the novels. I analyze the eclectic and intertextual nature of the novels, multiplicity of sources and references used in creating an image of Poland’s pagan past, and the result of using these particular tools in the context of the cycle’s ideological message. In a broader cultural context, the article postulates considering Slavic fantasy in the context of the folk turn.